2020
DOI: 10.3390/molecules25215059
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Chlorophyll a Monomer Incorporated into Cremophor EL Nano-Micelles under Dark and Moderate Light Conditions

Abstract: In this paper, stability of chlorophyll a monomers encapsulated into the Cremophor EL nano-micelles was studied under dark and moderate light conditions, typical of a room with natural or artificial lighting, in the presence of oxygen. The pigment stability against visible light was determined using the dynamic light scattering and molecular spectroscopy (UV-Vis absorption and stationary fluorescence) methods. Chlorophyll a, at the molar concentration of 10-5 M, was dissolved in the 5 wt% Cremophor emulsion fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Chlorophyll optical properties have been also exploited to verify the stability of the pigment encapsulated in cremophor-nano-micelles, to overcome the pigment hydrophobicity and facilitate its use as an additive in food or drugs [43]. The optical properties of chlorophyll and of its derivatives naturally present in alimentary oils extracted from fruits and seeds are also used as biomarkers for quality controls, as to kind of cultivar, country and adulteration [44][45][46][47].…”
Section: Chlorophyll As Photophysical Biomarkermentioning
confidence: 99%
“…Chlorophyll optical properties have been also exploited to verify the stability of the pigment encapsulated in cremophor-nano-micelles, to overcome the pigment hydrophobicity and facilitate its use as an additive in food or drugs [43]. The optical properties of chlorophyll and of its derivatives naturally present in alimentary oils extracted from fruits and seeds are also used as biomarkers for quality controls, as to kind of cultivar, country and adulteration [44][45][46][47].…”
Section: Chlorophyll As Photophysical Biomarkermentioning
confidence: 99%
“…It has also been reported that the discoloration of Chl was prevented in a nano-emulsion system wherein 5% of a nonionic surfactant (i.e., Cremophor EL) was employed (Janik et al, 2019(Janik et al, , 2020. This was attributed to the light stabilization of Cremophor EL through encapsulation of the monomerized Chl.…”
Section: Effect Of Axial Ligation To Mg In Chlorophyllmentioning
confidence: 99%
“…It has been reported that Chl exhibited photostability by the formation of nano-emulsions in the presence of nonionic surfactants (Janik et al, 2020(Janik et al, , 2019; such effects are also expected for emulsifiers. The purpose of this study is therefore to elucidate the effects of these selected emulsifiers on the discoloration of Chl and to determine the mechanism responsible for this effect.…”
Section: Introductionmentioning
confidence: 94%
“…Inspired by the early studies of chlorosomes, Tamiak et al [ 11 ] synthesized Zn-centered chlorin (Zn chlorin, or Znchl for short) by replacing the central Mg atom in chlorophyll-a [ 12 , 13 ] with a Zn atom to simulate Bchl c, the dominant component of chlorosomes in the nature. Znchl (see Figure 1 b) and Bchl c molecules have similar optical properties and can self-assemble into aggregate structures in non-polar solvents, but the former is much easier to synthesize.…”
Section: Introductionmentioning
confidence: 99%